Metal-organic frameworks (MOFs) in water filtration membranes for desalination and other applications - Kadhom, Mohammed; Deng, Baolin (Applied materials today, 2018)
[Display omitted] •MOFs membranes in water treatment are anticipated to grow up sharply.•MOFs membranes have different forms and ways of preparation.•MOFs neat pore size and special structures promote them for different applications.•MOFs membranes proved their durability in various water filtration processes.•Innovating new MOFs of high water stability will greatly contribute to the field. Accompanying with increases in population and economic activities in the world, the demand for water grows dramatically. Sea water covers two-thirds of the earth surface, so using this source to provide potable water is logical and should be an important component to solve the water shortage problem. Additionally, technologies exist to treat waste water to meet specific water quality requirements thus its reuse should also be fully explored to address the water shortage issue. Among different methods employed for desalination and waste water treatment/reuse, pressure driven membrane technologies are very common, in which undesirable constituents in water were rejected by a selective membrane barrier. Thereby, it is very important to study and develop membranes with highest separation and operation performance for the application. Metal-organic frameworks (MOFs) are materials of wide interests in recent years because of their interesting chemistry and potential applications. In separation science, researchers have extensively explored the use of MOFs for gas separation and water treatment. In this review paper, we plan to examine the usage of MOFs for the membrane desalination and water treatment, a relatively narrow but increasingly important area of MOFs applications. Following a short introduction about MOFs, we would present several methods to prepare MOFs membranes, various desalination techniques and the ways of MOFs application, and finally, MOF membranes in terms of their contributions to water filtration applications such as desalination, nanofiltration, ultrafiltration, and microfiltration. The use of MOFs in water treatment membranes is still in its infancy when compared with its applications for gas separation. Due to their structure and properties, however, MOFs had already demonstrated some amazing results enhancing membranes performance. With this review, the first on the topic to our knowledge, the purpose was to further stimulate the development and use of MOFs in water separation membranes and desalination.